2023
DOI: 10.1161/jaha.123.029899
|View full text |Cite
|
Sign up to set email alerts
|

Tmax Mismatch Ratio to Identify Intracranial Atherosclerotic Stenosis‐Related Large‐Vessel Occlusion Before Endovascular Therapy

Abstract: Background We aimed to clarify which time‐to‐maximum of the tissue residue function (Tmax) mismatch ratio is useful in predicting anterior intracranial atherosclerotic stenosis (ICAS)–related large‐vessel occlusion (LVO) before endovascular therapy. Methods and Results Patients with ischemic stroke who underwent perfusion‐weighted imaging before endovascular therapy for anterior intracranial LVO were divided into those with ICAS‐related LVO and those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The study found that ICAS-related LVO had smaller areas of hypoperfusion compared to embolization-related LVO, which is consistent with prior investigations ( 22 , 32 ). Contrary to embolization-related LVO, EVT for ICAS-related LVO is associated with a higher incidence of intraoperative reocclusion, an extended operating time, elevated mortality rates, and reduced revascularization rates ( 33 ).…”
Section: Discussionsupporting
confidence: 92%
“…The study found that ICAS-related LVO had smaller areas of hypoperfusion compared to embolization-related LVO, which is consistent with prior investigations ( 22 , 32 ). Contrary to embolization-related LVO, EVT for ICAS-related LVO is associated with a higher incidence of intraoperative reocclusion, an extended operating time, elevated mortality rates, and reduced revascularization rates ( 33 ).…”
Section: Discussionsupporting
confidence: 92%
“…Owing to robust collaterals, patients with ICAS-LVO are more likely to present with fluctuating symptoms and lower stroke severity compared with embolic LVO patients. 56,57 While the diagnosis of ICAS-LVO is commonly made intraprocedurally, some preprocedural imaging findings are important to evaluate and could help in establishing early diagnosis. On noncontrast computed tomography scan, the presence of calcification could be suggestive of ICAS.…”
Section: Icas-large Vessel Occlusionmentioning
confidence: 99%
“…The investigators found that a lower Tmax mismatch ratio of >10 seconds/>6 seconds (indicative of good collaterals) to be the optimal predictor of ICAS-LVO. 56 Finally, a number of studies attempted to provide prediction models to identify ICAS-LVO; however, most studies have modest sensitivity and specificity. [61][62][63][64] In a posthoc analysis of the DIRECT-MT trial (Endovascular Thrombectomy With or Without Intravenous Alteplase in Acute Stroke), the investigators created a predictive model for early diagnosis of ICAS-LVO, 65 which included the presence of atrial fibrillation history, hyperdense sign, and M2 occlusion to be negatively correlated with ICAS-LVO whereas the presence of hypertension, smoking, lower clot burden score, and occlusion of the M1.…”
Section: Icas-large Vessel Occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diagnostic performance of clinical and radiological biomarkers to detect underlying ICAD before EVT has not been systematically studied. Previous studies suggest that automated parameters of computed tomography perfusion (CTP) associated with a good collateral status are associated with underlying ICAD 5 9 .…”
Section: Introductionmentioning
confidence: 99%